Advances in Local Drug Delivery for Periodontal Treatment: Present Strategies and Future Directions - Mayuka Nakajima; Mayuko Yanagawa; Honoka Takikawa; Truong Tran Thien; Lorena Zegarra-Caceres; Chunyang Yan; Koichi Tabeta (Biomolecules, 2025)
Periodontitis is a highly prevalent, irreversible inflammatory disease characterized by the destruction of tooth-supporting tissues, eventually leading to tooth loss. Conventional treatment involves the mechanical removal of the subgingival biofilm, which is a major cause of gingival inflammation. However, the inaccessibility of deep-seated polymicrobial biofilms limits its effectiveness. Despite the adjunct use of systemic antimicrobials, their low site-specific bioavailability and systemic side effects remain concerns. Local drug administration offers a targeted alternative. However, the dynamic oral environment, which is characterized by continuous salivary and gingival crevicular fluid flow, poses challenges in maintaining therapeutic drug levels. Drug delivery systems (DDSs) provide technical solutions to overcome these limitations. With advancements in materials science and nanotechnology, diverse local DDS (LDDS) formulations tailored for periodontal applications have been developed. While traditionally focused on infection control, the application of LDDSs has expanded beyond antimicrobial therapy. Increasing attention has been paid to LDDS-based regenerative strategies, which aim to overcome the limitations of conventional regenerative therapies. This review aims to provide a comprehensive overview of the current and emerging DDS strategies in periodontal therapy, focusing on their applications in infection management and bone regeneration and discussing their limitations and prospects for clinical translation.